On the Ayed-Kuo stochastic integration for anticipating integrands - Jornet, Marc (Stochastic analysis and applications, 2023)
In this article, we prove new results for the anticipating stochastic integral introduced by Ayed and Kuo. We present an existence criterion for the integral, a Fubini's theorem, a Leibniz integral rule, and an alternative definition for a class of integrands.